Tantangan kontemporer organisasi masyarakat sipil dalam gerakan hak asasi manusia - Halili Halili (Universitas Negeri Yogyakarta, 2009)
Civil Society Organizations play a significant role in movement of human rights. CSO's face shifting contemporary challenges, namelY, betrayal against values of human rights and weaknesses of state sovereignty. These new challenges strive for CSO's to conduct some action in two ways: retrospective paradigm and prospective one. In one hand, they should do war against forget in the past violations of human rights. In the other hand, tbey have to respond progressivelY the future challenge of human rights.